How do you simplify the following expression in Sage? [closed]
By differentiating a function at 0, I got the following equation in Sage.
(b - f(0))*(c - f(0))*D[0](f)(0) - 1 == 0
How do I make Sage
Plug in f(0) = b+c
Simplify and solve for D0(0)?
I tried
equation = (b - f(0))(c - f(0))D0(0) - 1 == 0 new_equation = equation.subs({f(0): b+c}) solve(new_equation, D0(0))
I get the following error
Substitution using function-call syntax and unnamed arguments has been removed. You can use named arguments instead, like EXPR(x=..., y=...)